Rational Emotive Behavior Therapy (REBT) Guidelines To Reduce Student Aggressiveness - Dewi Aswira Putri; Frischa Meivilona Yendi; Taufik Taufik; Verlanda Yuca (Indonesian Counselor Association (IKI), 2019)
Aggressive behavior is a negative action that is intentionally done by individuals who try to hurt others both physically and verbally. There are many factors that influence adolescent aggression, ridicule, conflict in the family, unfavorable school environment, audio-visual media that show scenes of violence and individual perceptions of the environment. This aggressive behavior will affect the lives of individuals themselves and others. Based on this, guidance and counseling is very important to reduce the aggressive behavior of students. One of the guidance and counseling services that can be given group guidance by asking for rational emotive behavior (REBT). With this service, students are expected to behave positively according to applicable norms and not harm others.